PENGARUH KOMPOS DAN BIOCHAR TERHADAP FITOREMEDIASI TANAH TERCEMAR KADMIUM DARI LUMPUR LAPINDO MENGGUNAKAN KANGKUNG DARAT - Nina Dwi Lestari; Ahmad Nugraha Aji (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2020)
Lapindo Mudflow in Sidoarjo in 2006 brought heavy metals cadmium (Cd) that polluted the soil and environment around the affected area. Phytoremediation using water spinach (Ipomea reptans) is one of the alternatives to decrease the heavy metal pollution on Lapindo mud. The organic materials (compost and biochar) can also be used to reduce the contamination of heavy metals in soils. The aim of this study was to obtain the best composition of organic matter and biochar to support phytoremediation using water spinach plant in the cadmium-polluted soil. The study was conducted in a greenhouse with eight treatments consisted of four levels of organic matter application. The parameters measured were plant height, number of leaves, pH, CD content, and uptake of Cd. The results showed that there was a significant effect on the addition of compost and biochar on plant growth, Cd content, and Cd uptake. Results of the study showed that the addition of compost gave better results than that of biochar. The best treatment was on K7 (contaminated soil : compost : biochar; 1:1:1) for all parameters observed. Compared to the K0 (control) treatment, height of the plant increased up to 24%, the number of leaves increased up to 100%, the Cd content in the roots and shoots increased up to 44% and 95%, the content of the Cd in the planting media after the planting period decreased by 61%.